L’Auberge espagnole à la maison ou la médiation numérique au service de la mobilité internationale étudiante - Cécilia BRASSIER-RODRIGUES (Tic & Société)
In this article, we examine the ways in which digital information and communication technologies are accompanying the sustainable transformation of international student mobility, in a health context that requires adjustments to supervised periods abroad. We will see how these tools provide tremendous opportunities for overcoming constraints on some students who are unable to go abroad. We will explain how digital home-based internationalisation can increase the mobility capital of all students. In doing so, we argue in favour of a hybridisation of physical and virtual mobilities, that students can combine to enhance what we define as mobility pathways. A new mobile habitus is thus underway.